The Melanesian Way in South Pacific Regional Diplomacy: Implications for the Papua Issue - Elys Krisdiana (Papua Journal of Diplomacy and International Relations, 2026)
This article examines how the tension between Melanesian solidarity and state sovereignty shapes the Melanesian Spearhead Group’s (MSG) diplomacy on the Papua issue. Drawing on a qualitative research design, the analysis is based on interpretive document analysis of MSG leaders’ communiqués, ministerial statements, and official declarations issued between 2010 and 2022. The study is informed by constructivism and norm contestation theory to assess how competing norms are articulated and managed in regional practice. It offers a novel contribution to International Relations by reconceptualizing the Papua issue in MSG diplomacy not as a problem to be resolved, but as a condition sustained through ongoing norm contestation. The findings reveal that Melanesian solidarity legitimizes regional attention while state sovereignty constrains collective action, producing a dynamic interplay rather than convergence. By demonstrating that ambiguity, selective activation, and discursive balancing function as stabilizing mechanisms, this article challenges conventional assumptions that unresolved issues reflect institutional weakness and instead shows how they can sustain regional cohesion.   KEYWORDS Melanesian Spearhead Group; Diplomacy; Norm Contestation; Papua; Sovereignty.